2017
DOI: 10.1111/bph.13685
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐atherosclerotic effect of the angiotensin 1–7 mimetic AVE0991 is mediated by inhibition of perivascular and plaque inflammation in early atherosclerosis

Abstract: BACKGROUND AND PURPOSEInflammation plays a key role in atherosclerosis. The protective role of angiotensin 1-7 (Ang-(1-7)) in vascular pathologies suggested the therapeutic use of low MW, non-peptide Ang-(1-7) mimetics, such as AVE0991. The mechanisms underlying the vasoprotective effects of AVE0991, a Mas receptor agonist, remain to be explored. EXPERIMENTAL APPROACHWe investigated the effects of AVE0991 on the spontaneous atherosclerosis in apolipoprotein E (ApoE)À/À mice, in the context of vascular inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 65 publications
5
102
0
7
Order By: Relevance
“…Local inflammation has an important role in PVAT dysfunction, as shown by findings that PVAT inflammation preceded atherosclerotic plaque formation and endothelial dysfunction in apolipoprotein E −/− mice (Skiba et al . ). Dysfunctional PVAT obtained from animal models with obesity increases the expression of inflammatory cytokines and chemokines such as TNF, monocyte chemoattractant protein 1, interleukin‐6 and interferon gamma (Chatterjee et al .…”
Section: Discussionmentioning
confidence: 97%
“…Local inflammation has an important role in PVAT dysfunction, as shown by findings that PVAT inflammation preceded atherosclerotic plaque formation and endothelial dysfunction in apolipoprotein E −/− mice (Skiba et al . ). Dysfunctional PVAT obtained from animal models with obesity increases the expression of inflammatory cytokines and chemokines such as TNF, monocyte chemoattractant protein 1, interleukin‐6 and interferon gamma (Chatterjee et al .…”
Section: Discussionmentioning
confidence: 97%
“…AVE0991 was found to be 10-fold more potent than ANG (1–7) in competing for [ 125 I]-ANG (1–7) binding to, and 5-fold more potent than ANG (1–7) to induce NO release from bovine aortic endothelial cells [207], suggesting that AVE0991 may act as a nonpeptide agonist for the Mas receptor [208,209]. Subsequent in vivo studies have reported that AVE0991 significantly protected postischemic heart failure in rats [210], prevented diabetes-induced cardiovascular dysfunction [211], inhibited atherogenesis in apoE-knockout mice [212,213], ameliorated inflammation in experimental arthritis [214], and attenuated cardiac hypertrophy [215]. Despite these reported protective effects in different animal models or diseases, no clinical trial for AVE0991 is currently registered since it was developed more than 10 years ago [207].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
“…82 Nox2 NADPH oxidase mediates M1/M2 polarization and regulates their participation in vascular damage, inflammation, and fibrosis. 83,84 The interaction between tumor necrosis factor-α-like weak inducer of apoptosis (Tnfsf12) regulates vascular damage by stimulating ROS production in an Nox2-dependent manner in macrophages and can, therefore, promote accelerated vascular aging 85 and cognitive impairment. 86 There is increasing interest in unraveling the mechanisms of activation of immune cells in the vascular wall.…”
Section: Inflammatory Mechanisms Of Hypertension Are Linked To Oxidatmentioning
confidence: 99%